1983
DOI: 10.1192/bjp.143.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors and Affective Disorder: An Investigation of Brown and Harris's Model

Abstract: The aetiological model proposed by Brown and Harris was examined in a sample of 110 working class women with children in Oxford. Using the same methodology as Brown and Harris, the role of provoking agents in the onset of affective disorder was found to be very similar to that which they originally described. Lack of an intimate relationship with a husband or boyfriend was found to act as a vulnerability factor, increasing the risk of psychiatric disorder in the face of a provoking agent. There was a trend for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1
5

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 15 publications
3
33
1
5
Order By: Relevance
“…The present study is limited in its means to con tribute to such knowledge. The reason for this is that the definition employed already excluded possible social influences, although such links for manic-depressive phases and also for dysphoric states have been described several times [Campbell et al, 1983;Weissmann and Paykel, 1974;Bidzinska, 1984;Kennedy et ah, 1983]. We must therefore limit ourselves to the presentation of obser vations concerning possible psychopharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is limited in its means to con tribute to such knowledge. The reason for this is that the definition employed already excluded possible social influences, although such links for manic-depressive phases and also for dysphoric states have been described several times [Campbell et al, 1983;Weissmann and Paykel, 1974;Bidzinska, 1984;Kennedy et ah, 1983]. We must therefore limit ourselves to the presentation of obser vations concerning possible psychopharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…1982;Mur phy. 1982;Campbell et al" 1983); und c) bestimmte Persön lichkeitseigenschaften. Allerdings lassen sich diese nur schwer von depressionsbedingten Persönlichkeitsakzentu ierungen bzw.…”
Section: Zur Pathogenese Der Altersdepressionunclassified
“…In the third study Campbell et al (1983) studied 110 working-class women with at least one child living at home. The PSE was used to assess psychiatric illness; Brown & Harris' (1978) method was used to determine life stress, and three of their four vulnerability factors ('intimacy', 'three or more children at home' and 'lack of employment') were assessed.…”
mentioning
confidence: 99%
“…The alternative and more usual multiplicative model (Everitt & Smith, 1979) was not used. A fourth unpublished study (Cooke, 1981), documented by Campbell et al (1983), assessed a community sample of subjects and found no interaction between life events, assessed by means of Paykel et a/. 's measure (1969), and Brown & Harris' vulnerability factors.…”
mentioning
confidence: 99%